2020
DOI: 10.1177/1076029620974455
|View full text |Cite
|
Sign up to set email alerts
|

Anticardiolipin Positivity Is Highly Associated With Intrauterine Growth Restriction in Women With Antiphospholipid Syndrome

Abstract: The purpose of our study was to evaluate pregnancy outcomes of women with antiphospholipid antibodies (aPL) positivity and assess risk factors associated with adverse pregnancy outcomes. Pregnant women with aPL positivity were enrolled prospectively in China from January 2017 to March 2020. Treatment of low-dose aspirin and low molecular weight heparin were given. Pregnancy outcomes and coagulation function were recorded and compared with normal pregnancies. Multivariable logistic regression was performed to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Two studies compared APO in ncAPS and HC with inconclusive results. While one reported a similar rate of APO between groups (24), another study concluded that ncAPS patients had an increased risk of pregnancy complications compared to healthy pregnant women (25). Despite the limited information in terms of APO between ncAPS and HC, the overall rate of APO in both ncAPS and APS groups was higher than expected from the general comparator population of each study (26)(27)(28).…”
Section: Study Selectionmentioning
confidence: 85%
See 4 more Smart Citations
“…Two studies compared APO in ncAPS and HC with inconclusive results. While one reported a similar rate of APO between groups (24), another study concluded that ncAPS patients had an increased risk of pregnancy complications compared to healthy pregnant women (25). Despite the limited information in terms of APO between ncAPS and HC, the overall rate of APO in both ncAPS and APS groups was higher than expected from the general comparator population of each study (26)(27)(28).…”
Section: Study Selectionmentioning
confidence: 85%
“…low 19,22,25 quality evidence, described similar rates of pregnancy outcomes between ncAPS and APS groups after standard and non-standard APS treatments, whilst other two with very low 23 and low 24 quality of evidence did not. Less conclusive is the information about the rate of APO in ncAPS and APS patients before APS treatment.…”
Section: Outcome From Systematic Searchmentioning
confidence: 94%
See 3 more Smart Citations